Emerging therapeutic targets for schizophrenia: a framework for novel treatment strategies for psychosis - Sonnenschein, Susan F. (Expert Opin Ther Targets, 2020)
INTRODUCTION: Antipsychotic drugs that target the dopamine system have been central to the treatment of schizophrenia, but their limitations in efficacy, tolerability, and precision necessitate improved treatment strategies. Multiple lines of research have implicated glutamatergic dysfunction in the hippocampus as an early source of pathophysiology in schizophrenia. Novel compounds have been designed to treat glutamatergic dysfunction, but they have produced inconsistent results in clinical trials. AREAS COVERED: This review discusses how the hippocampus is thought to drive psychotic symptoms through its influence on the dopamine system. It offers the reader an evaluation of proposed treatment strategies including direct modulation of GABA or glutamate neurotransmission or reducing the deleterious impact of stress on circuit development. Finally, we offer a perspective on aspects of future research that will advance our knowledge and may create new therapeutic opportunities. PubMed was searched for relevant literature between 2010–2020 and related studies. EXPERT OPINION: Targeting the aberrant excitatory-inhibitory functioning observed in the hippocampus and its related circuits has the potential to both alleviate symptoms and reduce the risk of transition to psychosis if implemented as an early intervention. Longitudinal multimodal brain imaging combined with mechanistic theories generated from animal models can be used to better understand the progression of hippocampal-dopamine circuit dysfunction and factors related to heterogeneity in treatment response.